Координатно-чувствительный детектор заряженных частиц для спектроскопии - Sidorenko, V. P.; Prokofiev, Yu. V.; Murchenko, D. S.; Yeremenko, V. M.; Shelekhov, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2016)
The authors have designed, manufactured and tested a coordinate-sensitive detector for charged particle spectroscopy. The detector can be used in the devices for the elemental analysis of materials, providing simultaneous analysis of all the elemental composition with high sensitivity and precision. The designed device is based on an integrated circuit (IC) and a microchannel plate (MCP) electron multiplier. The IC is mounted on a ceramic substrate. Ions fall on the MCP mounted above the IC. Giving rise to a pulse which typically exceeds 106 electrons, each ion falls on the detector electrodes and these pulses are counted. In this research, a two stage stack of MCPs (Hamamatsu) was used. The MCPs have a channel diameter of 12 μm on a 15 μm pitch. The results of tests carried out in a mass spectrometer are presented. The designed detector is small, light, and low-power.